The mechanisms of tanshinone in the treatment of tumors - Zhang, Pengyu; Liu, Wendi; Wang, Yuan (Frontiers in Pharmacology, 2023)
Tanshinone is a lipophilic compound that is present in traditional Chinese medicine and is derived from the roots of Salvia miltiorrhiza (Danshen). It has been proven to be highly effective in combating tumors in various parts of the body, including liver carcinoma, gastric cancer, ovarian cancer, cervix carcinoma, breast cancer, colon cancer, and prostate cancer. Tanshinone can efficiently prevent the reproduction of cancerous cells, induce cell death, and inhibit the spread of cancerous cells, which are mainly involved in the PI3K/Akt signaling pathway, NF-κB pathway, Bcl-2 family, Caspase cascades, MicroRNA, MAPK signaling pathway, p21, STAT3 pathway, miR30b-P53-PTPN11/SHP2 axis, βcatenin, and Skp2. However, the properties and mechanisms of tanshinone's anti-tumor effects remain unclear currently. Thus, this study aims to review the research progress on tumor prevention and mechanisms of tanshinone to gain new perspectives for further development and clinical application of tanshinone.